Reversible spin-optical interface in luminescent organic radicals - Emrys Evans (Nature, 2023)
Molecules present a versatile platform for quantum information science and are candidates for sensing and computation applications. Robust spin-optical interfaces are key to harnessing the quantum resources of materials. To date, carbon-based candidates have been non-luminescent, which prevents optical readout via emission. Here we report organic molecules showing both efficient luminescence and near-unity generation yield of excited states with spin multiplicity S > 1. This was achieved by designing an energy resonance between emissive doublet and triplet levels, here on covalently coupled tris(2,4,6-trichlorophenyl) methyl-carbazole radicals and anthracene. We observed that the doublet photoexcitation delocalized onto the linked acene within a few picoseconds and subsequently evolved to a pure high-spin state (quartet for monoradical, quintet for biradical) of mixed radical–triplet character near 1.8 eV. These high-spin states are coherently addressable with microwaves even at 295 K, with optical readout enabled by reverse intersystem crossing to emissive states. Furthermore, for the biradical, on return to the ground state the previously uncorrelated radical spins either side of the anthracene shows strong spin correlation. Our approach simultaneously supports a high efficiency of initialization, spin manipulations and light-based readout at room temperature. The integration of luminescence and high-spin states creates an organic materials platform for emerging quantum technologies.